The problems in the communication process between NGOs and society - Miszkiel, Mariusz; Popławski, Tadeusz (Journal of the Belarusian State University. Sociology, 2020)
The article considers and analyses the specificity of social communication on the base of considerations about communication of aid organizations (for example Wspólnota Polska, Helsińska Fundacja Praw Człowieka, Zespół Monitorowania Rasizmu i Ksenofobii, Stowarzyszenie Interwencji Prawnej, Polskie Towarzystwo Prawa Antydyskryminacyjnego, Obywatele RP, Fundacja Otwarty Dialog, Komitet Obrony Demokracji, Akcja Demokracja and other) with the society. The article analyses this problem from a sociological point of view. Using the sociological analysis, the authors prove that communication, as one of the variables in the description and translation of social phenomena, also has another hidden function, thanks to which it becomes a specific term – a «picklock». A detailed description of the research and the selection of methods were included in previous studies, and there were also extensive accounts of the encountered actors regarding the nature and context of the observed situations of communication dilemmas. The research area was stretched between the periphery and social centers according to T. Popławski’s theory. The main focus here is on conclusions about communication and bureaucracy. The bureaucracy based on the Weberian model seems to be imploding more and more under the weight of extreme rationality, turning into irrationality. The authors sum the article up with practical advice on resolving the issues related to bureaucratism.
Keywords: social institutes; social communication; NGO; society; bureaucratism